ANALYSIS OF IMPLEMENTATION OF DIVERSION AND RESTORATIVE JUSTICE AS A FORM OF PROTECTION OF CHILDREN'S RIGHTS IN CONFLICT WITH THE LAW - Malagano, Tahura; Dainty, Andrew R.J. (EQUALEGUM International Law Journal, 2024)
Background. Restorative justice involves all parties involved in a crime working together to find solutions, focusing on children and the community, with the ultimate goal of creating restorative justice. The use of restorative justice and diversion as a means of defending the rights of minors in legal trouble, as well as the nature of the issue and its impediment, are major concerns in the study's purpose. Research Method. The normative approach and empirical jurisdiction are the methodological approaches employed in this work. The information used in this study was gathered from both field and library sources. Findings. The community of research conducted by the Correctional Center that the rights of children in conflict with the law are less protected at lower levels, ranging from examination of the investigation up to the trial, and the application of diversion and restorative justice as a form of protection of those rights. The application of law enforcement efforts to justice restorative running optimally is a solution to these constraints. One impeding factor is the lack of a common application of the law as the foundation and guide for all law enforcement agencies, as well as the inconsistent application of regulations in the field in the handling of children in conflict with the law. Conclusion. The initiative aims to promote restorative justice in legal cases involving children, transforming law enforcement's perspective from retributive and restitutive justice to a more equitable approach.